Penguatan Kreativitas Berwirausaha Melalui Praktik Pembuatan Lilin Aromaterapi Bagi Ibu-Ibu PKK Desa Kemplong Pekalongan: Model Inovatif Pemberdayaan Ibu Pkk Melalui Pelatihan Lilin Aromaterapi - Arsanti Mumtazah; Nahdiyatul Uyun; Amanda Salsabila; Nur Shihatus Sakinah; M. Mirza Muhaimin; Rusma Winursita; Eka Puji Rahayu; Arditya Prayogi; Riki Nasrullah (Journal of Research and Community Service, 2025)
This community service program aimed to strengthen entrepreneurial creativity and business awareness among members of the PKK women’s group in Kemplong Village, Pekalongan, through hands-on training in aromatherapy candle production as a form of locally based creative economic activity. The primary challenges faced by the community included limited productive skills, underutilization of household resources, and a lack of innovative income-generating initiatives with added economic value. The program employed a participatory and practice-oriented approach, encompassing needs assessment, coordination with local stakeholders, preparation of training modules, delivery of foundational materials, practical demonstrations of candle-making, mentoring through reflective discussions, and evaluation of outcomes. The results indicate a significant improvement in participants’ knowledge and skills in independently producing aromatherapy candles, accompanied by increased motivation and self-confidence to initiate home-based businesses. Participants successfully created candle products with basic variations in fragrance and form that demonstrated potential market value. Moreover, the activity fostered social interaction, collaboration, and collective engagement among PKK members, strengthening social capital as a foundation for future entrepreneurial development. The implications of this program suggest that practice-based training combined with mentoring serves as an effective model for community empowerment, particularly in promoting women’s creative entrepreneurship. This initiative may serve as a reference for similar programs by emphasizing sustainability, product innovation, marketing strategies, and long-term economic impact within local communities.